CLINICAL CHRACTERISTICS OF PATIENTS AND RESULTS OF CATHETER ABLATION IN ATRIAL FIBRILLATION IN RUSSIA: SUBANALYSIS OF THE EUROPEAN REGISTRY 2012-2016 - E. N. Mikhailov; N. Z. Gasymova; S. А. Bayramova; V. E. Kharats; O. N. Kachalkova; A. Yu. Dmitriev; R. E. Batalov; D. P. Morgunov; I. A. Silin; A. A. Aleksandrovskiy; D. V. Kryzhanovskiy; A. B. Romanov; et al. (Российский кардиологический журнал)
Aim. The results presented, of subanalysis of the catheter ablation (CA) registry in atrial fibrillation (AF) with the patients properties, specifics of CA and treatment results, in Russia comparing to European countries.Material and methods. During 2012 to 2015, totally 3742 patients included to the registry, of those 477 in Russia. In 467 Russian patients (males 56,5%; mean age 58,5 y. o.) CA AF was done. During one year 392 patients were followed up. Minimum requirements to follow-up: routine ECG registration and non less than one contact after 12 months passed.Results. In Russian patients there were more common obesity (46,1% and 29,2%, p<0,001), hypertension heart disease (40,2% and 22,8%, p<0,0001), coronary heart disease (31,7% and 16,2%, p<0,0001), chronic heart failure (67,3% and 13,0%, p<0,0001). In Russia the patients more commonly underwent primary CA (83,5% in Russia and 77,6% in European countries, p<0,05), more rare in Russia the cryoballoon ablation was done (3% and 18%, p<0,05). Generally adverse events were reported more rare in Russia (10,5% and 16,6%, p=0,0007), including cardiovascular adverse events (2,6% and 5,2%, p<0,05). Tachiarrhythmias recurs were diagnosed more rare in Russia, including by the subsutaneous ECG monitors (17% and 1,6% in other countries, р<0,001). Within the year of follow-up, full absence of tachiarrhythmias recurs in Russia was found in 65,8% of patients, in other countries — in 74,7% (р=0,0003).Conclusion. In real clinical setting, high efficacy of CA AF was shown, resistant to antiarrhythmic therapy. In most of Russian patients there were cardiovascular comorbidities. There was lower rate of reported adverse events in Russian centers of interventional treatments.